Comparative study of intravaginal misoprostol versus dinoprostone gel for induction of labour in primigravida - Dulewad, Shirish S.; Haritha, Chitikala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Labour is an inevitable consequence of pregnancy. The aim of the present research was to study the safety, efficacy and effect of intravaginal misoprostol and dinoprostone gel for induction of labour. Methods: 300 patients who required induction of labour in a tertiary care centre were included in this prospective randomized controlled study from August 2019 to August 2021 with a study duration of 12 months. 50% of cases received 25 µg of intravaginal misoprostol and repeated for a maximum of 6 doses every 4 hours as needed. 50% cases received 0.5 mg dinoprostone gel and repeated for maximum of 2 doses every 6 hours as needed. The patients selected were evaluated initially by modified Bishop’s score and admission test for fetal wellbeing. After drug insertion, patients were monitored for fetal heart rate, vital signs, progress of labour. A partogram was strictly maintained in all patients. Results: The highest number in both groups being below 40 weeks which were 74% and 76% in dinoprostone and misoprostol groups respectively. Rest were between 40.1-41.6 weeks. The mean induction delivery interval in dinoprostone was more (16.15±3.1) than in misoprostol (12.26±2.21). Requirement of oxytocin augmentation was less in misoprostol group than dinoprostone group. Caesarean section rate was less in misoprostol group. Maternal side effects were minimal in either groups and neonatal outcome was good in both the groups. Conclusions: Both misoprostol and dinoprostone gel are safe, effective for cervical ripening and induction but misoprostol is more cost effective and stable at room temperature.